BUSINESS DEVELOPMENT STRATEGY USING SWOT ANALYSIS METHOD IN OCTOPUS CRACKER PRODUCTION - Hafiza, Nurul; Romdhon, M Mustopa; Irawan, Andi; Asriani, Putri Suci (Fakultas Pertanian dan Bisnis, Universitas Kristen Satya Wacana, 2024)
Kaur Regency with its high octopus potential, produces a derivative product namely octopus crackers, by the IKM Putra Daerah with the product name kerupuk gurita maknyos (Kuritos). This research aims to formulate the appropriate strategies for the development of the kerupuk gurita maknyos (Kuritos) business in Linau Village, Maje District, Kaur Regency. The data analysis technique used is qualitative, employing an inductive thinking method, and data analysis utilizing SWOT analysis. The position of the Maknyos octopus cracker business (Kuritos) is in quadrant I (aggressive), thus the environmental factors influencing the development of Kuritos crackers in Linau Village are the factors that constitute strengths and opportunities for the business. The recommended strategic formulations include utilizing attractive product packaging and promoting a love movement for regional products to increase sales both offline and online, with support from SME training provided by the government to enhance market penetration. It also suggests utilizing bazaars and becoming event sponsors to enhance exposure to quality products, while expanding distribution through the use of existing business permits for market expansion beyond the region, maintaining sustainable and quality raw materials, fostering good relationships with suppliers through the utilization of communication infrastructure for supply chain optimization, and optimizing production processes with modern technology, while utilizing counseling facilities to improve production efficiency and quality.